150 years of Observatory in Arcetri - Bianchi, Simone (Il Colle di Galileo, 2023)
To coincide with the 150th anniversary of the Astrophysical Observatory of Arcetri, the inaugural speech of the director and founder Giovanni Battista Donati is reproduced. Keywords. Arcetri, 150 years, celebrations, GB Donati